Interactive generator: a self-powered haptic feedback device - Badshah, A.; Gupta, S.; Cohn, G.; Villar, Nicolas; Hodges, Steve; Patel, S.N. (Proceedings of the 2011 annual conference on Human factors in computing systems, 2011)
We present Interactive Generator (InGen), a self-powered wireless rotary input device capable of generating haptic or force feedback without the need for any external power source. Our approach uses a modified servomotor to perform three functions: (1) generating power for wireless communication and embedded electronics, (2) sensing the direction and speed of rotation, and (3) providing force feedback during rotation. While InGen is rotating, the device is capable of providing the sensation of detents or bumps, changes in stiffness, and abrupt stops using only power that is harvested during interaction. We describe the device in detail, demonstrate an initial ‘TV remote control’ application, and end with a discussion of our experiences developing the prototype and application. To the best of our knowledge, InGen is the first self-powered device, which also provides haptic feedback during operation. More broadly, this work demonstrates a new class of input systems that uses human-generated power to provide feedback to the user and wirelessly communicate sensed information.